Web and big data : APWeb-WAIM 2017 International Workshops: MWDA, HotSpatial, GDMA, DDC, SDMA, MASS, Beijing, China, July 7-9, 2017, Revised selected papers /: APWeb-WAIM 2017 International Workshops: MWDA, HotSpatial, GDMA, DDC, SDMA, MASS, Beijing, China, July 7-9, 2017, Revised selected papers. (2017) - Unknown
No abstract available